(untitled) (Journal of Statistical Research, 2025)
In mathematics a random walk (also known as drunkard’s walk) is a succession of random steps. In 1905 Karl Pearson introduced the term “random walk”. A Bernoulli random walk is the random walk on the integer number line Z which starts at 0 and at each step moves +1 or −1 with equal probability. A Pearsonian random walk is a walk in the plane that starts at the origin 0 and consists of length 1 taken in uniformly random direction. In this paper several known and new results of Bernoulli and Pearsonian walks will be presented. Journal of Statistical Research 2025, Vol. 59, No. 1, pp. 47-64